Maximum Principle for Mean-Field FBSDEs with Mixed Initial-Terminal Conditions. (10th May 2022) - Li, Ruijing
Abstract : The present paper concerns with optimal control problems allowing for time inconsistent utility functions of mean-field FBSDEs with mixed initial-terminal conditions. Moreover, the control variable enters the diffusion coefficient, and the control domain is with nonconvexity. Via extended Ekeland's variational principle as well as the reduction method, a general stochastic maximum principle is established in the framework of mean-field theory. Finally, a linear-quadratic example is worked out to illustrate the application of the results.